دراسة مقارنة لنتائج تعلم اللغة العربية بين المنهج 13 ومنهج ميرديكا في ديلي سردانج - Saddiah, Saddiah; Zaky, Ahmad; Ulum, Bahrul (TSAQOFAH, 2025)
This research investigates the differences in Arabic language learning outcomes between students following Curriculum 13 at State Senior High School 2 Deli Serdang and those following the Merdeka Curriculum at State Senior High School 1 Deli Serdang. It aims to determine whether there are statistically significant differences between the two groups. The researcher employed a quantitative method using the ex post facto approach. A sample of 60 students was selected through simple random sampling, with 30 students from each school. Data were collected using an achievement test on the topic of "Hajj and Umrah" in Arabic, as well as interviews and observations. The data were analyzed using the Mann-Whitney test due to the data's lack of homogeneity and non-normal distribution, as indicated by normality and homogeneity tests. The analysis, conducted with SPSS 21, revealed a significance value of 0.512, which is greater than 0.05. This indicates that the null hypothesis is accepted and the alternative hypothesis is rejected, meaning there is no significant difference in Arabic learning outcomes between students of the two curricula. The study concludes that the limited understanding among teachers regarding the implementation mechanisms of the Merdeka Curriculum contributed to the lack of outstanding learning outcomes. Therefore, it is essential to enhance teacher training and development programs to ensure the effective implementation of the curriculum and to achieve higher levels of proficiency in Arabic language learning.